STRATEGY OF OPTIMALIZATION CASH WAQF IN INDONESIA - Nadya, Prameswara Samofa; Alwyni, Farouk Abdullah; Hadiyati, Puji; Iqbal, Muhammad (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2018)
This study aims to identify various problems of cash waqf management in Indonesia. Identification of these various problems is expected to be formulated by various alternative solutions. Based on the research, it was identified that there were three main obstacles in the process of optimizing cash waqf, namely socialization, regulations and Nazhir, all of which were broken down in several sub-problems. The solutions that can be offered from these three constraints are socialization programs, both on understanding and cash waqf mechanisms, improving existing cash waqf regulations, specifically on the role of BWI and funding for the development of cash waqf, as well as programs designed to improve capacity asset management for Nazhir. Based on this solution, the strategy that can be carried out is more comprehensive and coordinated socialization, making regulations that can optimize the role of BWI and also optimize funds for the development of cash waqf, and continuous improvement of Nazhir's competency